The effects of wheat pill poisoning (aluminum phosphide) dosage on arterial blood gases and their clinical outcome - Ali, Sajjad; Ahmad, Ishtiaq; Ashraf; Islam, Zohra; Shah, Syed Kashif Ali; Ali, Nayab (Journal of the Pakistan Medical Association, 2023)
Objective: To analyse the effects of aluminum phosphide poisoning dosage on arterial blood gases and the clinical outcome. Method: The cross-sectional study was conducted at the intensive care unit of Mardan Medical Complex, Mardan, Pakistan, from January 2021 to May 2022, and comprised patients of either gender who had attempted suicide using aluminum phosphide. Data was collected using a predesigned questionnaire. Data was analysed using SPSS 26. Results: Of the 116 patients, 42(36.2%) were males and 74(63.8%) were females. There were 75(64.65) survivors; 31(41.33) males and 44(58.66) females with overall mean age 26.30±9.45 years. There were 41(35.35%) non-survivors; 11(26.82%) males and 30(73.18) females with overall mean age 28.21±11.16 years.During hospitalisation, the non-survivors showed drastically decreased levels of all arterial blood gas paramters with severe clinical outcomes (p<0.05). As the number of aluminum phosphide pills increased, the chance of survival decreased (p<0.05). The non-survivors spent an average of 32.51±16.02 hours in hospital (range: 6-59 hours). Conclusion: Patients who ingested more aluminum phosphide pills had more abnormal arterial blood gas parameter with severe clinical outcomes. Also, they had lower chance of survival and unfavorable response to treatment. Key Words: Aluminum phosphide, Poisoning, Emergency management, Critical care.